Introduction to management science - Stevenson, William J. (Homewood, Illinois : Irwin Inc., 1989)
This is an introductory textbook on the use of quantitative models that can be used to describe and solve certain kinds of problems that confront managers.
Part one : Linear programming -- Part two : Stochastic models -- Part three : Decision making and information systems.
Includes index.
Keywords: MANAGEMENT SCIENCE